CRAFT TRAINING IS THE MAIN CONDITION FOR PRESERVING OUR TRADITIONS - Marasulova I. M. (European Science Publishing, 2024)
The article talks about learning a craft as the main condition for preserving our traditions.
Keywords: craft, youth, traditions.